Ordinary differential equations: students' difficulty in solve the algorithm of the initial value problem with the integrating factor method - Farlina, E; Rachmawati, T K; Ariany, R L; Widiastuti A, T T; Sobarningsih, N (IOP conference series. Materials Science and Engineering, 2018)
The algorithm of mathematical proof is very important possessed by students, especially in Mathematics Education Study Program in Differential Equation. One of the materials in Differential Equations is the integral factor. Many students have difficulties on the material factor of integral. This study aims to (1) analyze student errors in terms of mathematical proof capability on the material factor of integral, (2) analyze the difficulties faced by students in the algorithm. Subjects subjected to research are 33 sixth semester students of Mathematics Education Program UIN SunanGunungDjati Bandung totalling 33 students. This research is a qualitative research. Data collection by using the test is a test of mathematical proof of material factor of integral. The results showed that 65% of students were unable to complete the proof, 35% of the students did not use the proof algorithm, and all the students did not perform the verification check